Deciphering the protein digestion of meat products for the elderly by in vitro food oral processing and gastric dynamic digestion, peptidome analysis and modeling. Issue 16 (25th June 2021) - Peyron, M-A.; Sayd, T.; Sicard, J.; Mirade, P-S.; Pinguet, J.; Chambon, C.; Santé-Lhoutellier, V.
Abstract : FODP: Food Oral and Digestive Processing. Abstract : The elderly population will increase sharply in the future, along with an emerging range of specific nutritional needs that include adapted food. We aimed to develop a workflow to study the fate of a food, objectify the bioavailability of nutrients in the case of the digestive physiology of the elderly, and model the fate of proteins in the stomach. Pork frankfurters were subjected to in vitro normal and deficient mastication and gastric digestion, mimicking adult and elderly food oral and digestive processing. Swallowable food boluses were characterized for granulometric and rheological properties. Biochemical analyses were conducted on the bolus and on the digesta. Macronutrients, label-free peptide quantification and identification were performed, and modeling was applied to protein digestion kinetics. After deficient mastication, the food bolus was harder with more large particles, lower free iron release and more protein oxidation. The amount of peptides released in the stomach progressively increased, but to a lower extent for the elderly digestive condition and irrespective of masticatory efficiency. 592 peptides were identified from 67 proteins. Different trajectories were observed for adult and elderly digestive conditions, and two groups of meat proteins were identified based on the rate of hydrolysis. Designing suitable foods requires in vitro tools to evaluate the possible benefit for the elderly. Besides the well-known notion of Food Oral Processing (FOP), our work broadens the concept by extending oral activity to digestion when working in a nutritional context. This new concept is named Food Oral and Digestive Processing, FODP.